Hubungan antara pengetahuan dan perilaku menjaga kesehatan gigi dengan oral hygiene pada mahasiswa Program Studi Pendidikan Dokter Gigi Fakultas Kedokteran Universitas Udayana - N.W. Rossa Sri Astini; D.N Ari Susanti; Steffano Aditya Handoko (Bali Dental Journal, 2019)
Introduction: Oral hygiene is one of important determinant for health as oral hygiene could affect various important functions such as speech, masticatory function and aesthetic. Students of dentistry in particular should able to apply the knowledge and behavior of maintaining healthy teeth and mouth of their own. The purpose of this study is to know the relation between knowledge and behaviour of maintaining dental health with oral hygiene of Dentistry Student at Medical Faculty of Udayana University. Method: Research method was analytical observational using cross sectional design. The subject of research was selected by total sampling method on Dentistry Student at Medical Faculty of Udayana University, thus 100 students were selected through inclusion and exclusion criterias. This research was conducted by giving questionnaire covering questions about knowledge and behavior and Oral Hygiene Index Smplified (OHI-S) was used as examination tool and as an indicator in asessing oral hygiene. Result: Significance correlation was documented for relationship between knowledge and oral hygiene using Chi-square test (p=0.026) and similar result also documented between oral hygiene and behavior of maintaining oral hygiene (p=0.006). Conclusion: From those results in this study, could be concluded that there is a relationship between knowledge and behaviour of maintaining dental health with oral hygiene on Dentistry Student at Medical Faculty of Udayana University.